The study of safety audit at departments in Health Campus Universiti Sains Malaysia Kubang Kerian, Kelantan - Marabi, Siti Aishah Nor (Universiti Sains Malaysia, 2016)
The primary purpose of this research was to study the compliance on Occupational Safety, Environment Health, Organization Management, and Occupational Welfare aspect based on OSHA 1994 (act 514), FMA 1967 (act 139), EQA 1974 (act 127), UBBL 1984 and Ministry of Health requirement. The first step of the research was data collection from 42 departments conducted through the safety audit form combining from DOSH, NIOSH, and MOH. Number of 42 from 56 Department in Health Campus USM is done as respondent from Head of Department, Sister and Chief Supervisor. The result of normality test is p>0.05. Then there are significant comparisons mean by Occupational Management, Occupational Safety, Environmental Health and Occupational Welfare among 3 Departments that have been categorize. Seconds, comparison means by department among of Occupational Management, Occupational Safety, Environmental Health and Occupational Welfare, Lastly, comparison of mean percentage among 3 categorical departments. The comply sum is as 90.90% from 38 departments and non-complies as 9.09% from 4 departments that are get the low marks in Safety Audit. Conclusion, the result of the study showed that the percentage of compliance is moderate. Therefore the further enforcement on compliance to the act by the legislation authority should be conduct in frame time in order to enhance the great result to identify the hazard of safety and health at work place.